Proof of Principle: Is a Pre-treatment Behavior Approach Test a Potential Predictor for Response to Intensive Residential Treatment in Patients With Treatment Refractory Obsessive Compulsive Disorder? - van Geijtenbeek-de Vos van Steenwijk, Malinda; de Leeuw, Aart; van Megen, Harold; Selier, Jonathan; Visser, Henny (Frontiers in Psychiatry, 2021)
Patients with severe and treatment refractory obsessive compulsive disorder (OCD) are usually referred to a specialized center for intensive residential treatment (IRT), consisting of exposure and response prevention (EX/RP), pharmacotherapy and additional therapies. About 50% of the patients does not respond to IRT. Currently we are not able to predict treatment response. If we were to have predictive tools, we could personify treatment at an earlier stage. Recent studies show that early adherence and willingness to EX/RP and low avoidance during EX/RP measured during treatment were associated with treatment response. In this observational study willingness and ability of patients with severe and treatment refractory OCD (N=58) is conceptualized by a behavioral measurement, measured before the start of 12 weeks of IRT, using a Behavior Approach Test (BAT), as opposed to relying on self-report measurements. A medium or strong association between pre-treatment performance on the BAT and treatment response would justify next steps to test the BAT as a predictive tool for IRT. Results of regression analyses showed that there is a significant association between the performance on the BAT and change in OCD symptom severity after IRT. However, the effect-size is too small to use the BAT in its current form as predictor in clinical practice. The principle of the association between pre-treatment behaviorally measured willingness and ability to fully engage in EX/RP, and treatment response has now been proven. To ultimately design a predictive tool, future research is needed to refine a behavioral measurement of pre-treatment willingness and ability.